Cellular Automata and Discrete Complex Systems 19th International Workshop, AUTOMATA 2013, Gießen, Germany, September 17-19, 2013. Proceedings - Kari, Jarkko; Kutrib, Martin; Malcher, Andreas; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
The volume LNCS 8155 constitutes the refereed proceedings of the 19th International Workshop on Cellular Automata and Discrete Complex Systems, AUTOMATA 2013, held in Giessen, Germany, in September 2013. The 8 papers presented were carefully reviewed and selected from 26 submissions. The scope of the workshop spans the following areas the theoretical and practical aspects of a permanent, international, multidisciplinary forum for the collaboration of researchers in the field of Cellular Automata (CA) and Discrete Complex Systems (DCS), to provide a platform for presenting and discussing new ideas and results, to support the development of theory and applications of CA and DCS (e.g. parallel computing, physics, biology, social sciences, and others) as long as fundamental aspects and their relations are concerned, to identify and study within an inter- and multidisciplinary context, the important fundamental aspects, concepts, notions and problems concerning CA and DCS.
Invited Papers -- Conceptual Connections around Density Determination in Cellular Automata -- A Guided Tour of Asynchronous Cellular Automata -- A Note on the Classification of the Most Simple Asynchronous Cellular Automata -- A Survey on m-Asynchronous Cellular Automata -- Regular Papers -- Elementary Cellular Automata with Memory of Delay Type -- A Robustness Approach to Study Metastable Behaviours in a Lattice-Gas Model of Swarming -- Leakage Squeezing Using Cellular Automata -- 1- Resiliency of Bipermutive Cellular Automata Rules -- On the Convergence of Boolean Automata Networks without Negative Cycles -- Color Blind Cellular Automata -- Commutators of Bipermutive and Affine Cellular Automata -- On Polynomial Rings in Information Dynamics of Linear CA.
Keywords: Computer science; Computer communication systems; Data structures (Computer science).; Computers; Algorithms; Computer simulation; Computer Science; Computation by Abstract Devices; Algorithm Analysis and Problem Complexity; Simulation and Modeling; Computer Communication Networks; Data Structures, Cryptology and Information Theory; Computer Science, general; Electronic books